2013
DOI: 10.4321/s1135-57272013000200009
|View full text |Cite
|
Sign up to set email alerts
|

Comparación de las aplicaciones de Google y Yahoo para la geocodificación de direcciones postales con fines epidemiológicos

Abstract: RESUMENFundamentos: Geocodificar es asignar coordenadas geográficas a puntos del espacio, frecuentemente direcciones postales. El error cometido al aplicar este proceso puede introducir un sesgo en las estimaciones de modelos espacio-temporales en estudios epidemiológicos. No se han encontrando estudios que midan este error en ciudades españolas. El objetivo es evaluar los errores en magnitud y direccionalidad de dos recursos gratuitos (Google y Yahoo) respecto a GPS en dos ciudades de España.Método: Se geocod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
(8 reference statements)
0
5
1
1
Order By: Relevance
“…Notice, however, that most previous studies have used the coordinates obtained using hand-held GPS receivers as the gold-standard – accuracy around 10–20 meters – rather than cadastral maps, which are much more accurate – accuracy of 1 meter for a 1/2000 scale map. Regarding the recently available GE batch AG tool, to our knowledge, only one study addressed its positional error (still relative to GPS measurements) [17] . Authors reported a median error of 22 meters, slightly higher than our estimate.…”
Section: Discussionmentioning
confidence: 99%
“…Notice, however, that most previous studies have used the coordinates obtained using hand-held GPS receivers as the gold-standard – accuracy around 10–20 meters – rather than cadastral maps, which are much more accurate – accuracy of 1 meter for a 1/2000 scale map. Regarding the recently available GE batch AG tool, to our knowledge, only one study addressed its positional error (still relative to GPS measurements) [17] . Authors reported a median error of 22 meters, slightly higher than our estimate.…”
Section: Discussionmentioning
confidence: 99%
“…Geocoding residential addresses can be performed using three methods. A first method consists in using online geocoding services to obtain subjects’ coordinates or to create online maps with subjects’ residence locations [ 29 , 30 ]. These free services are available on the Internet and do not require specific expertise in geocoding [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that have previously explored the feasibility and the quality of geocoding residential addresses of an existing cohort in a European context were conducted on small populations (i.e. n = 30 [ 29 ], n = 100 [ 27 ] or n = 354 [ 13 ]). Moreover, these studies did not explore the accuracy of geocoding over various geographical areas (urban or rural) or time periods.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 300 handwritten addresses were randomly selected from the cohort database but stratified by municipality to ensure that each municipality was adequately represented in the subsample (200 selected in Temuco and 100 in Padre Las Casas). The number of addresses evaluated was limited to 300 for it was a feasible amount to process using the reference method, allowed adequate comparison, and because similar numbers have been used in previous studies 2,7,21 . Addresses were limited to urban areas within the municipalities using the same inclusion criteria as the larger study.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%